Pernikahan di Bawah Umur dalam Perspektif Hukum Positif di Indonesia: Tradisi di Tana Toraja - Angelina, Sandra Laudya; Efriliani, Firial Tiara; Oktaviani, Risa Dewi; Octaviani, Eky; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
This research examines underage marriage in the perspective of positive law in Indonesia in the traditions of Tana Toraja. The purpose of this research is to find out how the existing laws and regulations in Indonesia are related to the marriage of minors and to know and understand what forms of legal protection are given if underage marriage has occurred. The method used in this research is the normative juridical research method, which means that the problems studied are based on laws and regulations, legal literature, and the media. The results showed that there are still high cases of underage marriage in Tana Toraja because it is influenced by local customary law that violates Law Number 1 of 1974 jo Law Number 16 of 2019 concerning Marriage. Therefore, an active role is needed from the government and the community in order to create a balance between cultural preservation and compliance with national law.